Lobbying Regulations and Political Equality in the American States. (March 2015) - Flavin, Patrick
Laws that regulate the conduct of professional lobbyists in statehouses across the nation are one attempt to ensure that citizens' opinions receive more equal consideration when elected officials make policy decisions. Do states with stricter lobbying regulations actually display more egalitarian patterns of political representation? Using public opinion measures from the National Annenberg Election Surveys and data on state policies, this article first demonstrates that state policy decisions are consistently more proximate to the opinions of affluent citizens. I then evaluate the relationship between the stringency of state lobbying regulations and representational equality across the states and find evidence that states with stricter regulations weigh citizens' opinions more equally in the policymaking process. These findings suggest that lobbying regulations can play an important role in promoting greater political equality.